2020
DOI: 10.1111/jvs.12940
|View full text |Cite
|
Sign up to set email alerts
|

Do regeneration traits vary according to vegetation structure? A case study for savannas

Abstract: Aim: Regeneration traits are crucial for understanding patterns and processes in plant communities. However, regeneration traits are not reported much in community ecology, preventing a better assessment of trait-based community assembly. Here we assessed habitat-related regeneration traits by comparing species from open (grassland and shrubland) and closed (woodland) Brazilian savannas (cerrado). Location: Our study site comprised two cerrado areas in southeastern Brazil that range from open to closed vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Species dispersal syndromes (a proxy of spatial dispersal capacity) were classified according to Pérez-Harguindeguy et al (2013) and Escobar et al (2018Escobar et al ( , 2021a as: zoochory, species with fleshy fruits or fleshy structures partially or totally enclosing seeds, or fruits and seeds that contain appendages (e.g. hooks, sticky substances) that attach to animals; anemochory, species with winged or flat diaspores with a large area:volume ratio (e.g.…”
Section: Dispersal Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Species dispersal syndromes (a proxy of spatial dispersal capacity) were classified according to Pérez-Harguindeguy et al (2013) and Escobar et al (2018Escobar et al ( , 2021a as: zoochory, species with fleshy fruits or fleshy structures partially or totally enclosing seeds, or fruits and seeds that contain appendages (e.g. hooks, sticky substances) that attach to animals; anemochory, species with winged or flat diaspores with a large area:volume ratio (e.g.…”
Section: Dispersal Syndromementioning
confidence: 99%
“…Conversely, unpredictable dry spells during the rainy season and spatial variation in microhabitat suitability can increase seedling mortality, favoring the emergence and maintenance of risk-reduction strategies that spread seedlings in time and/ or space (Engelbrecht et al 2006, Salazar et al 2012, Buoro and Carlson 2014. Previous research in the cerrado has shown that almost half of species have non-dormant seeds (Ramos et al 2017, Escobar et al 2018, 2021a, a proportion much higher than expected for a seasonally dry environment (Baskin and Baskin 2014). This could be caused by phylogenetic inertia (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenology is an Essential Biodiversity Variable (EBV) that has been elected among the key traits to evaluate the health of the natural system worldwide (Morellato et al 2016;Kissling et al 2018). Therefore, the consideration of traits such as flowering and fruiting times associated with seed dispersal, seasonal germination strategies and pollination will certainly have positive implications for restoration practice (Viani et al 2015;Buisson et al 2017;Bennett et al 2019;Fisk et al 2019;Escobar et al 2021).…”
Section: Phenological Patterns In Restored Areas and Forest Fragmentsmentioning
confidence: 99%
“…The Baskin and Baskin (2004) paper has been cited numerous times in the literature, which indicates that the Nikolaeva-Baskin system is being widely used by seed biologists. Especially noteable is that this system has been used to determine (1) proportional distribution (dormancy profile) of the five classes of dormancy and of nondormancy in various vegetation regions (biomes) on earth and in different kinds of plant communities (Baskin and Baskin, 1998, 2014aSautu et al, 2007;Torres, 2008;Schwienbacher et al, 2011;Kos et al, 2012;Sommerville et al, 2013;Souza et al, 2015;Carta, 2016;Dayrell et al, 2016;Lan et al, 2018;Escobar et al, 2021;Fernández-Pascual et al, 2021;Liu et al, 2021;Zupo et al, 2021), (2) proportional distribution of desiccation-sensitive seeds in relation to dormancy class (Tweddle et al, 2003), (3) phylogenetic relationships/evolution of the five classes of seed dormancy (Willis et al, 2014), (4) class of seed dormancy in relation to life-history traits including dispersal (Sautu et al, 2006(Sautu et al, , 2007Salazar et al, 2011;Sánchez et al, 2015;Souza et al, 2015;Vandvik et al, 2017;Escobar et al, 2018;Soltani et al, 2018b;Costea et al, 2019) and ( 5) the class of dormancy of seeds used in ecological restoration and conservation projects, as a guide to how to break dormancy (Silveira, 2013;Erickson et al, 2017;Kildisheva et al, 2019Kildisheva et al, , 2020Zanetti et al, 2020). Also, dormancy formulae have been used to show in detail the step-by-step changes that occur during dormancy break in seeds with de...…”
Section: Introductionmentioning
confidence: 99%